The Role of Financial Inclusion and Economic Growth on Poverty in Developing Countries in Asia - Annisa Putri, Dian; Fitrawaty, Fitrawaty; Ruslan, Dede (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2024)
This research aims to determine the influence of financial inclusion and economic growth on sustainable development in developing countries in Asia. This research method uses quantitative research. This research was conducted on the International Monetary Fund and World Bank websites. The type of data used in this research is secondary data. Where the data collected comes from necessary websites such as the International Monetary Fund. Data collected from this website is used for the financial inclusion and poverty variables obtained from the International Monetary Fund website. Meanwhile, the scope of this research is developing countries in Asia such as Armenia, Indonesia, India, Iran, and Thailand with a research data series for 8 years, namely from January 2015 to December 2022. The variable data collection method comes from websites related to variables. study. Meanwhile, the type of data used in this research is a time series, where the data is a time series. Data analysis technique multiple regression analysis. Pooled Least Square (Common Effect), Random Effect Model Approach, Determination of Panel Data Regression Model Tests, Chow Test, Hausman Test, Lagrange Multiplier Test, Statistical Test Analysis, Parameter significance testing, F statistical test, individual significance test (t-test), analysis of assumption tests consisting of autocorrelation test, multicollinearity test, heteroscedasticity test. The research results show that panel data estimation results used the Fixed Effect Model (FEM) to see the role of financial inclusion and economic growth on poverty in developing countries in Asia, proven by the two independent variables with financial inclusion as indicators of commercial bank branches, outstanding loans, outstanding deposits and proven economic growth. does not affect poverty in developing countries in Asia. Whether the indicators are commercial bank branches, outstanding loans, outstanding deposits, and economic growth, these four variables do not have a probability of < 0.05.